Septal Infusions of the Hyperpolarization-Activated Cyclic Nucleotide-Gated Channel (HCN-Channel) Blocker ZD7288 Impair Spontaneous Alternation But Not Inhibitory Avoidance. - Cissé, Ramata S.; Krebs-Kraft, Desiree L.; Parent, Marise B. (Behavioral Neuroscience, 2008)
Blockade of septal hyperpolarization-activated cyclic nucleotide-gated channels (HCN) impairs hippocampal theta, an effect that would be expected to impair memory. To test this hypothesis, the present experiments determined whether septal infusions of the selective HCN channel blocker ZD7288 would impair performance on two memory tasks that involve the septo-hippocampal system: spontaneous alternation (SA) and continuous multiple inhibitory avoidance (CMIA). Fifteen minutes prior to assessing SA or CMIA, different groups of male Sprague-Dawley rats were given septal infusions of saline or ZD7288 (0.2, 0.6 or 1.5 μg/0.5 μl). Septal infusions of ZD7288 impaired SA in a dose-dependent manner; the same infusions did not affect CMIA acquisition or retention. These results appear to be the first demonstration that HCN channels in the medial septum influence memory. Specifically, they suggest that septal HCN channels play a permissive role in spatial working memory, but do not influence emotional long-term memory. Given that these channels are preferentially located on GABA septo-hippocampal projection neurons, the present data provide further evidence that these projection neurons are involved in memory. Reprinted by permission of the publisher.